Joint Statement on the Role of Respiratory Rehabilitation in the COVID-19 Crisis: The Italian Position Paper - Vitacca, Michele; Carone, Mauro; Clini, Enrico Maria; Paneroni, Mara; Lazzeri, Marta; Lanza, Andrea; Privitera, Emilia; Pasqua, Franco; Gigliotti, Francesco; Castellana, Giorgio; Banfi, Paolo; Guffanti, Enrico; et al. (Respiration, 2020)
Due to the exponential growth of the number of subjects affected by coronavirus disease 2019 (COVID-19), the entire Italian health care system had to respond promptly and in a very short time with the need of semi-intensive and intensive care units. Moreover, trained dedicated COVID-19 teams consisting of physicians were coming from different specialties (intensivists or pneumologists and infectiologists), while respiratory therapists and nurses have been recruited to work on and on without rest. However, due to still limited and evolving knowledge of COVID-19, there are few recommendations concerning the need in respiratory rehabilitation and physiotherapy interventions. The presentation of this paper is the result of a consensus promoted by the Italian societies of respiratory health care professionals who contacted pulmonologists directly involved in the treatment and rehabilitation of COVID-19. The aim was to formulate the more proper and common suggestions to be applied in different hospital settings in offering rehabilitative programs and physiotherapy workforce planning for COVID-19 patients. Two main areas of intervention were identified: organization and treatment, which are described in this paper to face the emergency.